Carrying Capacity Assessment Based on Chlorophyll-a in the Tanjung Balam Lake, Siak Hulu Sub-District, Kampar District Riau Province - Hidayatunnisah, Putry; Simarmata, Asmika Harnalin; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract The carrying capacity is defined as the ability of aquatic environment to support the life of organisms in that area. A study aimed to assess the aquatic carrying capacity for extensive fishing in the Tanjung Balam Lake, Buluh China Village, Kampar District, Riau. The carrying capacity was determined based on primary productivity using chlorophyll-a value. A research was conducted June, 2019. There were 3 stations namely station 1 (inlet area), station 2 (in the middle of lake) and station 3 (tip of lake). In each stations, there were 2 sampling point, in the surface and depth of 2 Secchi (90 cm). Sampling was done three times, once a week. Water quality parameters measured were chlorophyll-a concentration, transparency, temperature, pH, dissolved oxygen, phosphate and nitrate concentration. Results shown that chlorophyll-a: 6.87 – 25.28 µg/L, transparency: 49 – 54 cm, temperature: 28.5 – 29.8 0C, pH: 5, dissolved oxygen: 3.2 – 7.3 mg/L, CO2 3.9 – 15.9 mg/L, phosphate: 0.042 – 0.148 mg/L and nitrate: 0.0125 – 0.0437 mg/L. Carrying capacity assessment based on chlorophyll-a in the Tanjung Balam Lake was 0.46 tons/year.Keywords: Kampar River, Oxbow lake, Primary Productivity, Water quality